Pengaruh Net Profit Margin (NPM) Dan Earning Per Share (EPS) Terhadap Harga Saham - Frieska Septiany; Suhono Suhono (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This study aimed to analyze the effect of Net Profit Margin (NPM) and Earning per share (EPS) on stock prices either partially or simultaneously in the Ceramic, Porcelain and Glass Sub-Sector Listed on the Indonesia Stock Exchange for the 2012-2018 period. The research method used is a quantitative method with a descriptive and verification approach. The data analysis method used is statistical analysis using SPSS software. The independent variables used in this study are Net Profit Margin (NPM) and Earnings per share (EPS). While the dependent variable used in the study is the stock price. The results showed, the results of multiple linear regression analysis, namely, Y = 163.323 +(-0.033) + 0.149 + e. The results of the T test showed that the Net Profit Margin has a value of tcount> t table that is 0.646> 0.05, and Earnings per share has a value of tcount> t table that is 7.616> 2.042. Simultaneously, the variables of Net Profit Margin (NPM) and Earning per share (EPS) have a significant effect on stock prices. While partially there is a significant effect of Net Profit Margin (NPM) and Earnings per share (EPS) on Stock Prices in the Ceramic, Porcelain and Glass Sub-Sector Listed on the Indonesia Stock Exchange. Keywords: Net Profit Margin, Earnings Per Share, Share Price